Rasio Keuangan dan Pengaruhnya Terhadap Harga Saham Syariah dengan Price Earning Ratio Sebagai Variabel Moderasi - Yuliawati Yuliawati; Darmawan Darmawan (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
The purpose of this research was to examine the effect of EPS and ROE on stock price with PER as a moderating variable. The object examined was the company went public in the Jakarta Islamic Index period January 2010 - May 2018. The research period in this study was 8 years from 2010-2017. The sampling method in this research is purposive sampling to obtain 6 of company in Jakarta Islamic Index. This research used panel data regression and residual data. Based on the results of the analysis it was found that the Earning Per Share (EPS) and Return on Equity (ROE) have a significant effect on stock prices partially and simultaneously. In addition, Price Earning Ratio (PER) was able to moderate the relationship beetwen Earning Per Share (EPS) on stock prices. Finally, Price Earning Ratio (PER) was able to moderate the the relationship between Return on Equity (ROE) and stock prices.